Alterations of Both Dendrite Morphology and Weaker Electrical Responsiveness in the Cortex of Hip Area Occur Before Rearrangement of the Motor Map in Neonatal White Matter Injury Model - Ueda, Yoshitomo; Bando, Yoshio; Misumi, Sachiyo; Ogawa, Shino; Ishida, Akimasa; Jung, Cha-Gyun; Shimizu, Takeshi; Hida, Hideki (Frontiers in Neurology, 2018)
Hypoxia-ischemia (H-I) in rats at postnatal day 3 causes disorganization of oligodendrocyte development in layers II/III of the sensorimotor cortex without apparent neuronal loss, and shows mild hindlimb dysfunction with imbalanced motor coordination. However, the mechanisms by which mild motor dysfunction is induced without loss of cortical neurons are currently unclear. To reveal the mechanisms underlying mild motor dysfunction in neonatal H-I model, electrical responsiveness and dendrite morphology in the sensorimotor cortex were investigated at 10 weeks of age. Responses to intracortical microstimulation (ICMS) revealed that the cortical motor map was significantly changed in this model. The cortical area related to hip joint movement was reduced, and the area related to trunk movement was increased. Sholl analysis in Golgi staining revealed that layer I–III neurons on the H-I side had more dendrite branches compared with the contralateral side. To investigate whether changes in the motor map and morphology appeared at earlier stages, ICMS and Sholl analysis were also performed at 5 weeks of age. The minimal ICMS current to evoke twitches of the hip area was higher on the H-I side, while the motor map was unchanged. Golgi staining revealed more dendrite branches in layer I–III neurons on the H-I side. These results revealed that alterations of both dendrite morphology and ICMS threshold of the hip area occurred before the rearrangement of the motor map in the neonatal H-I model. They also suggest that altered dendritic morphology and altered ICMS responsiveness may be related to mild motor dysfunction in this model.